Diagnostic value of integrating salivary and blood miRNAs for pancreatic cancer detection - Wilson, Parker; Nonaka, Taichiro (Frontiers in Oncology, 2025)
BackgroundPancreatic cancer remains one of the most lethal malignancies due to its late-stage diagnosis and limited treatment options. Conventional diagnostic methods, such as imaging and tissue biopsy, often lack sensitivity in early-stage detection and are invasive, limiting their widespread application. There is an urgent need for non-invasive, highly accurate biomarkers to facilitate early diagnosis and improve patient outcomes. Circulating microRNAs (miRNAs) have emerged as promising liquid biopsy biomarkers, offering the potential for early detection through minimally invasive methods. This meta-analysis aims to evaluate the diagnostic performance of blood- and saliva-derived miRNAs in detecting pancreatic cancer.MethodsA systematic search of PubMed, Web of Science, and Scopus databases identified 350 relevant studies. After removing duplicates and applying eligibility criteria, 27 studies with 1,496 patients were included. These studies contained 168 sub-studies, each assessing the diagnostic potential of individual miRNAs. Quality assessment was conducted using the QUADAS-2 tool, and meta-analysis was performed using a random-effects model. Sensitivity, specificity, diagnostic odds ratio (DOR), and summary receiver operating characteristic (SROC) curves were analyzed to determine diagnostic performance.ResultsBlood-derived miRNAs demonstrated a pooled sensitivity of 0.83 (95% CI: 0.78-0.88) and specificity of 0.87 (95% CI: 0.82-0.91), while saliva-derived miRNAs exhibited slightly higher sensitivity at 0.87 (95% CI: 0.84-0.90) and specificity at 0.86 (95% CI: 0.82-0.89). The combined analysis yielded a sensitivity of 0.86 (95% CI: 0.84-0.89) and specificity of 0.85 (95% CI: 0.83-0.88). The area under the curve (AUC) for blood-derived miRNAs was 0.92 (95% CI: 0.89-0.94), whereas saliva-derived miRNAs achieved an AUC of 0.93 (95% CI: 0.90-0.95). The combined analysis resulted in an AUC of 0.92 (95% CI: 0.90-0.94). Diagnostic odds ratios were 33.40 (95% CI: 17.88-62.37) for blood-derived miRNAs, 39.94 (95% CI: 28.66-55.67) for saliva-derived miRNAs, and 37.04 (95% CI: 27.66-49.60) for the combined dataset.ConclusionBoth blood- and saliva-derived miRNAs exhibit strong diagnostic performance for pancreatic cancer, with saliva-derived miRNAs demonstrating slightly higher accuracy. These findings support the potential of circulating miRNAs as non-invasive biomarkers that could address the current limitations in pancreatic cancer diagnosis. Further large-scale, well-controlled studies are warranted to confirm these results and optimize their clinical application.